Fire Retardancy and Thermogravimetric Kinetics of Thiol-Ene Degradation as Affected by Added 9, 10-Dihydro-9-Oxa-10-Phosphaphenanthrene-10-Oxide (DOPO). Issue 1 (2nd January 2022) - Chen, Shiqi; Bao, Xiaohui; Wu, Fangyi; Wang, Jiangbo
Abstract: The fire retardancy of a thiol-ene (trimethylolpropane tris(3-mercaptopropionate)-pentaerythritol allyl ether, PTE) polymer was enhanced by the incorporation of fire retardant 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). The cone calorimetry results showed that, compared with pure PTE, the peak heat release rate (PHRR) and total heat release (THR) of the PTE composite at 5 wt% DOPO loading were reduced by 40.9% and 21.8%, respectively. The Kissinger and Flynn-Wall-Ozawa methods were both employed to analyze the TGA data of the PTE and fire-retardant PTE (FRTE) composites. It was clearly observed that the activation energies of pure PTE and the FRTE composites calculated using the two methods followed the same trend; the activation energies of the fire retardant PTE were lower than those of pure PTE, which we attribute to the fire retardant DOPO improving the thermal stability and fire retardancy of PTE.